Odonata Diversity at Sumber Clangap and Sumber Mangli Puncu Village Sub District of Puncu District of Kediri - Muhammad Muhibbuddin Abdillah; Tatag Bagus Putra Prakarsa; Esti Tyastirin (Jurnal Biodjati, 2019)
Sumber Clangap and Sumber Mangli are geographically located at the Mount Kelud steeps. Administratively located at Puncu Village, Puncu Sub-district and District of Kediri. They provided hab-itat for the flora than fauna especially Odonata that never been stud-ied before. We aimed to study Odonata diversity at Sumber Clangap and Sumber Mangli area. The method used in this study was natural snapshot experiment that conducted by Odonata monitoring. Micro-climate parameter including air temperature and humidity were not-ed. Odonata activity and behavior noted for analysis. Collected data were analyzed using Shannon-Wiener heterogeneity index. The results showed that there were 17 species from the whole location. There was Euphaea variegata, Vestalis luctuosa, Rhinocypha anisoptera, Peric-nemis stictica, Pseudagrion pruinosum, Coeliccia membranipes, Gy-nacantha subinterrupta, Idionyx montana, Paragomphus reinwardtii, Heliogomphus drescheri, Neurothemis fluctuans, Orthetrum glau-cum, Orthetrum pruinosum, Orthetrum sabina, Pantala flavescens, Trithemis festiva and Zygonyx ida. Based on the Shannon-Wiener heterogeneity index the value, Sumber Clangap had heterogeneity in-dex higher (H’=1,97) than Sumber Mangli (H’=1,39). Sumber Man-gli has a Java endemic species Paragomphus reinwardtii and Rhi-nocypha anisoptera that is spread only at Sumatera and East Java.